2021
DOI: 10.18421/tem104-32
|View full text |Cite
|
Sign up to set email alerts
|

Success and Challenges in MOOCs: A Literature Systematic Review Technique

Abstract: The rapid evolution of massive open online courses (MOOCs) has attracted widespread media coverage to the propensity of conventional education methods to disrupt readily available and free or cheap content delivery. MOOCs enable the possibility to offer students, even throughout the leastserved parts of the globe, access to high-quality learning. MOOCs are progressively seen as a possibility for millions worldwide who want free or low-cost educational opportunities. The students just required a well-establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Specifically, students perceived that Coursera has many high-quality courses and degrees (M = 5.10, SD = 1.606). This was consistent with several previous studies by Chansanam et al [48] and Scott [49], who found that Coursera provided learners with access to a variety of courses and degrees from top universities that cater to different learning needs and interests. Students also stated that Coursera has a high expert level and good academic support (M = 5.08, SD = 1.629), which was consistent with research by Alraimi, Zo, and Ciganek [16] and Jansen et al [50] that found Coursera learners value the diversity of experts who instruct courses on the platform because it gives them access to different viewpoints and insights.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, students perceived that Coursera has many high-quality courses and degrees (M = 5.10, SD = 1.606). This was consistent with several previous studies by Chansanam et al [48] and Scott [49], who found that Coursera provided learners with access to a variety of courses and degrees from top universities that cater to different learning needs and interests. Students also stated that Coursera has a high expert level and good academic support (M = 5.08, SD = 1.629), which was consistent with research by Alraimi, Zo, and Ciganek [16] and Jansen et al [50] that found Coursera learners value the diversity of experts who instruct courses on the platform because it gives them access to different viewpoints and insights.…”
Section: Discussionsupporting
confidence: 92%
“…(Millar et al, 2012). There will be a resistance reaction and rejection of the rules that will be implemented; this is one of the reasons why most changes are ineffective (Chansanam et al, 2021). On the other hand, according to (Aosa, 1992), the success of a corporation depends on achieving goals by transforming the input available to the organization into output.…”
Section: High-performance Human Resource Practices and Work Engagementmentioning
confidence: 99%